Covariates of vaginal microbiota and pro-inflammatory cytokine levels in women of reproductive age - Novak, J. [UNESP]; Ferreira, C. S.T. [UNESP]; Golim, M. A. [UNESP]; Silva, M. G. [UNESP]; Marconi, C. [UNESP] (Brill Academic Publishers, 2023)
This study aimed to assess the correlation between covariates of the vaginal microbiota and local levels of proinflammatory cytokines in women of reproductive age presenting four molecularly defined bacterial community-state types (CSTs). We enrolled 133 non-pregnant women who attended primary care health clinics for routine Pap-testing. Molecular profiling of vaginal microbiota was performed by V3-V4 16S rRNA sequencing. The covariates of vaginal microbiota included were: vaginal pH, total bacterial cell count, diversity (Shannon index), -richness and dominant taxa abundances. Levels of interleukin (IL)-1β, IL-6, IL-8, and tumour necrosis factor (TNF-α) were measured by enzyme-linked immunosorbent assays in supernatants of cervicovaginal fluids. Nonparametric Kruskal-Wallis test was used to compare microbiota covariates and cytokines among different CSTs. Spearman's tests were performed to assess correlations across the measured parameters. A total of 96 (72.2%) participants had CSTs dominated by Lactobacillus spp. (Lactobacillus crispatus CST I, n=38; Lactobacillus gasseri CST II, n=20; and Lactobacillus iners CST III, n=38). A total of 37 (27.8%) presented the Lactobacillus-depleted CST IV. Total bacterial count was higher in CST II (1.29E+05, 3.40E+04-6.69E+05) compared to other Lactobacillus-dominated CSTs (p=0.0003). The highest values of microbiota diversity (1.85; 0.23-2.68) and richness (27.0; 5.0-37.0) were observed in CST IV (P<0.0001). Lower levels of IL-1β were observed in CST I (5.4; 0.0-3,256) when compared to CST III (51.7; 0.0-2,616) and to CST IV (56.2; 0.0-3,407) (P=0.008). Levels of IL-6 were higher in CST II (4.13; 0-131.4) than in CST IV (0.0-58.27) (P=0.02). Correlation tests showed an overall distinct profile of CST II when compared to other Lactobacillusdominated CSTs, particularly regarding the correlation between total bacterial load and cytokines (r>0.39). In conclusion, this study provides evidence of a single pro-inflammatory signature of L. gasseri-dominated microbiota in response to bacterial load. Further studies evaluating a broader range of inflammation markers are warranted.
Keywords: 16s rRNA sequencing; bacterial count; bacterial diversity; bacterial vaginosis; Lactobacillus spp.